FACTORS ASSOCIATED WITH THE BIRTH COMPANION'S SATISFACTION WITH THE CARE PROVIDED TO THE PARTURIENT WOMANFATORES - Bruna Daniela Batista; Odaléa Maria Bruggemann; Carolina Frescura Junges; Manuela Beatriz Velho; Roberta Costa (Universidade Federal do Paraná, 2017)
The aim was to assess the birth companion's satisfaction with the care provided to the woman during labor and birth, and to calculate the associated factors. It is a cross-sectional study, undertaken in a University Hospital in the South of Brazil. In all, 369 companions were interviewed between March and September 2015. The associations were investigated with bivariate analyses and crude and adjusted odds ratio, using logistic regression. Satisfaction was most frequent in companions who did not witness violence to the woman during labor (adjOR 16.05; CI95% 6.35-40.52) and birth (AdjOR 14.25; CI95% 4.81-42.20), who were present during labor which culminated in vaginal birth (AdjOR 2.84; CI95% 1.31-6.17), who considered that the woman's wishes were respected (AdjOR 8.16; CI95% 3.41-19.54) and that her complaints were responded to (AdjOR 3.21; CI95% 2.07-4.99). The health professionals' relationships, attitudes and conducts influenced the companions' satisfaction with the care provided to the woman, independently of their sociodemographic characteristics.